Plasma composition control by mixture pellets at ASDEX Upgrade. (19th December 2018) - Lang, P.T.; Drenik, A.; Dux, R.; Jackson, T.; Kardaun, O.J.W.F.; McDermott, R.M.; Ploeckl, B.; Prechtl, M.; Rohde, V.; Ruess, R.R.; Schneider, P.A.; Schubert, M.; et al.
Abstract: Experiments were performed that aimed to control the plasma isotopic mixture by delivering supplemental components into the plasma via pellet injection. Pellets, mm-sized solid bodies of frozen fuel, are either formed from a mixture of different hydrogen isotopes or from deuterium (D) with added elements. Mixed HD pellets were produced reliably and reproducibly providing the required 1:1 ratio of the protium (H) and D, mimicking the situation in a future fusion reactor with D and tritium (T). By applying pellet fuelling, control of the plasma isotope composition was established while gaining access to the reactor-relevant high-density regime. However, the approach was mainly to demonstrate the controlling capability. Yet, experiments provided information on the impact of the isotopic composition on the plasma performance. There is a strong indication that adding H to a D reference plasma causes a reduction of both the particle and energy confinement. The deleterious impact of H on the particle confinement is, apparently, even stronger than on the energy confinement. Furthermore, small amounts of H can cause a loss of energy confinement that is stronger than anticipated by the H98( y, 2) scaling, which is usually employed in reactor design studies. In the course of this experiment, pellets were demonstrated to be an effective and powerful tool for detailed investigations of the isotope effect. A first test demonstrated that producing and launching pellets that contain a mixture of different elements is a feasible technique. The latter was achieved by doping a D host pellet despite technical reasons limiting the permissible amount of processed N.